The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/14680874211018363
|View full text |Cite
|
Sign up to set email alerts
|

Enabling robust simulation of polyoxymethylene dimethyl ether 3 (PODE3) combustion in engines

Abstract: PODE3 reaction mechanism developments are still in the early stages with very limited research. In particular, reaction mechanisms to characterize PODE3 combustion are neither sufficiently compact nor robust for 3D numerical simulations. Hence, the current work seeks to develop a compact yet reliable PODE3 reaction mechanism, embedded with appropriate chemistry to describe polycyclic aromatic hydrocarbon reactions. A decoupling methodology has been employed to achieve the desired outcome. The final mechanism c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 127 publications
0
0
0
Order By: Relevance
“…Several studies showed the potential of these fuels to achieve emission reduction objectives in different facilities, such as engines [5][6][7][8] and optical vessels [9,10]. Among these fuels, oxymethylene dimethyl ethers (OME n ) are attractive due to their physicochemical properties [11]. Their molecular structure is CH 3 -O-(CH 2 -O) n -CH 3 , where n explicitly the chain length (n = 1-6) directly affects the physicochemical properties of the fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the potential of these fuels to achieve emission reduction objectives in different facilities, such as engines [5][6][7][8] and optical vessels [9,10]. Among these fuels, oxymethylene dimethyl ethers (OME n ) are attractive due to their physicochemical properties [11]. Their molecular structure is CH 3 -O-(CH 2 -O) n -CH 3 , where n explicitly the chain length (n = 1-6) directly affects the physicochemical properties of the fuel.…”
Section: Introductionmentioning
confidence: 99%